SMART MONEY KIDS: PENDAMPINGAN LITERASI KEUANGAN ANAK UNTUK MEMBANGUN KARAKTER HEMAT DAN BIJAK - Syarifah, Wardatus; Fitriani, Nur Eka; Rohmah, Wasilatur (Universitas Al-Amien Prenduan, 2024)
This community service activity aims to foster financial literacy from an early age through the Smart Money Kids program, which focuses on developing thrifty and wise character traits in managing the pocket money of elementary school children. Children's low awareness of the importance of saving and managing finances is a problem that is often encountered in primary education, especially in rural areas. The methods used in this activity included initial observation, interactive counseling, educational games (financial games), and practical guidance on managing pocket money through simple economic simulations. A participatory approach was used to get children actively involved and help them understand the concept of the value of money, needs versus wants, and the importance of saving. The results of the activity showed an increase in children's understanding of basic financial concepts and a change in behavior towards wiser money management. In addition, the involvement of teachers and parents helped reinforce the sustainability of thriftiness in children's daily lives. The Smart Money Kids program proved to be effective as a character-based financial literacy learning model that can be widely implemented in primary education institutions.